О новых тенденциях в криминалистической методике расследования преступлений - Тищенко, Валерий Владимирович; Тіщенко, Валерій Володимирович; Tishhenko, Valerij (My University, 2009)
In the article the basic new tendencies of scientific researches are considered in the criminalistics method of investigation of crimes. A m o n g the theoretical issues of the day question of development of general method of investigation, classification of m e t h o d s of investigation, introduction in the concept apparat of criminalistics, category, is selected «technology of i n v e s t i g a t i o n s The special attention is spared the problem of principles of forming of separate m e t h o d s of investigation in science and practical activity.
Тищенко В. В. О новых тенденциях в криминалистической методике расследования преступлений / В. В. Тищенко // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 260-269.
Keywords: криминалистическая методика; расследование преступлений; криминалистическая классификация; принципы формирования методик расследования; криміналістична методика; розслідування злочинів; технологія розслідування; криміналістична класифікація; принципи формування методик розслідування; criminalistics method; investigation of crimes; technology of investigation; criminalistics classification; principles of investigation m e t h o d s forming